KAJIAN SEMIOTIK PAKAIAN DINAS UPACARA (PDU) PASUKAN PENGIBAR BENDERA PUSAKA (PASKIBRAKA) INDONESIA - Afrida Nurhawa, - (2020)
The Development of Character Education for the Indonesia National Flag Hoisting Troops (Paskibraka)'s Official Flag Ceremony Uniform (PDU) is one example of how clothing can be a means of non-verbal communication. The signs on Indonesia PDU Paskibraka's carry special meanings, so it needs to be studied so that users and observers can find out the message conveyed or desired. The purpose of this research is to obtain structural design data, decorative, signifier, signified, icon, index, symbol and denotative and connotative meaning. The method used is a semiotic study with a qualitative-interpretive type of research. The findings of this semiotic study show that PDU Paskibraka's has some of the same structural designs on the attributes and some of the milineris. The colors used are white, black, red, yellow, green and gold. Almost all of the materials used have a rough, stiff and hard texture. Another finding is the meaning obtained from the results of the semiotic assessment based on structural design, color and material. The signs in PDU Paskibraka generally represent state icons such as Ir.Soekarno, soldiers, and knights. All three have a nationalist character, love the country, are not afraid of death, a strong leadership spirit, etc. The impression that comes from the men's PDU Paskibraka is masculine, manly, and tough. At woman's PDU Paskibraka , the impression that arises is feminine, flexible, and graceful. For Paskibraka wearing a veil has the impression of being devout and religious. Icons (icons), index (index), and symbols (symbols) in structural design have different classifications. The denotation meaning that is present is the literal meaning of the structural design. The meaning of connotation is another meaning of the structural design. Keywords: Semiotic Study, Official Flag Ceremony Uniform (PDU), Indonesia National Flag Hoisting Troops (Paskibraka).